Eradicating Aggression in Muslim Society: A Special Guidance from Shaikh Sa‘adī's Teachings - Shahina Imran; Dr. Allah Ditta; Hafiz Muhammad Hasnain Asadi (International Research Journal of Arabic and Islamic Studies, 2022)
Shaikh Sa‘adī, a renowned Persian poet, is widely recognized for his works on ethics and morality. His teachings have been a source of inspiration for people across the globe, particularly in promoting peace and eradicating aggression in society. Today, his teachings continue to hold relevance, and many people turn to his teachings for guidance in leading a peaceful life. Sa‘adī's teachings emphasize the importance of empathy, kindness, and respect for others. He believed that these values are essential in creating a peaceful and harmonious society. One of his famous quotes, "Human beings are members of a whole, in the creation of one essence and soul," highlights the importance of unity and the interconnectedness of all individuals. This teaching emphasizes the need for individuals to work together and support each other, rather than engage in conflicts and aggression. Furthermore, Sa‘adī's teachings also focus on the role of forgiveness in promoting peace. He believed that forgiveness is a powerful tool that can be used to resolve conflicts and reconcile relationships. His teachings on forgiveness encourage individuals to let go of grudges and resentments and to approach others with a compassionate and forgiving attitude. Many individuals and organizations have utilized Sa‘adī's teachings to promote peace and eradicate aggression in society. For example, schools and universities have integrated his teachings into their curriculum to instill moral values in students. Similarly, social and religious organizations have used his teachings to promote interfaith harmony and peaceful coexistence. In conclusion, Shaikh Sa‘adī's teachings continue to hold relevance in promoting peace and eradicating aggression in society. His emphasis on empathy, kindness, respect, unity, and forgiveness offers valuable guidance in creating a harmonious and peaceful world.